Catalytic reforming of biomass pyrolysis tar using the low-cost steel slag as catalyst. (15th December 2019) - Guo, Feiqiang; Liang, Shuang; Zhao, Xingmin; Jia, Xiaopeng; Peng, Kuangye; Jiang, Xiaochen; Qian, Lin
Abstract: In this work, the possibility of steel slag as an effective and low-cost catalyst for the decomposition of biomass pyrolysis tar has been explored based on the high content of iron oxides for sustainable syngas production from biomass. By simple calcination treatment at 800 °C, the loose structure of the steel slag was formed with the main chemical composition of Fe2 O3 and MgFe2 O4 . The steel slag exhibited good catalytic activity on the cracking of biomass pyrolysis tar, and even higher tar conversion efficiency can be obtained by reusing the steel slag, leading to the increase in syngas yield. The presence of additional steam can further promote the tar reforming reactions, leading to the significant increase in H2 and CO. At 800 °C, the tar conversion efficiency reached 94.1% with a high gas yield of 493.5 mL/g. The interaction between steel slag and reductive gases resulted in the reduction of iron oxides into Fe3 O4, and more pores were formed for the spent steel slag, which can enhance the contact between active sites and reactants. These characteristics indicate that steel slag has the potential to be used as an efficient catalyst with excellent stability in the long-term biomass tar removal applications. Highlights: The steel slag after calcination were used for biomass tar reforming. Excellent catalytic performance was obtained for the tar conversion into syngas. Higher tar conversion efficiency can be obtained by reusing the steel slag. Iron oxides can be reduced to form stable and new porous structure.